Pengaruh Disiplin Preventif Dan Rotasi Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening Di Unit Pengelola Sampah Terpadu Dinas Lingkungan Hidup Provinsi DKI Jakarta - Camilia Amanda; Muhammad Richo Rianto; Choiroel Woestho; Muhammad Asif Khan; Eri Bukhari (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to determine the influence of preventive discipline and work rotation on employee performance through job satisfaction as an intervening variable in the Integrated Waste Management Unit of the DKI Jakarta Province Environmental Service. In this research, researchers used quantitative methods with research hypothesis testing carried out using outer model and inner model tests in SEM-PLS with the help of the SmartPLS version 4.0 program which is useful for analyzing the effect of preventive discipline and work rotation on employee performance through job satisfaction as an intervening variable. in the Integrated Waste Management Unit of the DKI Jakarta Provincial Environmental Service using 150 respondents who were distributed through questionnaires in the Integrated Waste Management Unit area of the DKI Jakarta Provincial Environmental Service. The results of the research that has been carried out are as shown in the following brief explanation: (1) The Preventive Discipline Variable (X1) influences Employee Performance (Y). (2) The Job Satisfaction variable (Z) influences employee performance (Y). (3) The Job Rotation Variable (X2) influences Employee Performance (Y). (4) The Preventive Discipline Variable (X1) influences Employee Performance (Y) through Job Satisfaction (Z). (5) The Job Rotation Variable (X2) influences Employee Performance (Y) through Job Satisfaction (Z).